ANALISIS BIAYA DAN PENDAPATAN KEBUN KARET (Havea brasiliensis) DI DESA JILATAN ALUR KABUPATEN TANAH LAUT KALIMANTAN SELATAN - Rinda Bangun Subekti; Magdalena Yoesran; Rina Muhayah Noor Pitri (Universitas Lambung Mangkurat, 2021)
Knowing the total costs, revenues and profits of rubber concessions obtained during the period of exploitation. Knowing the magnitude of the interest rate that produces a profit equal to zero (no profit / no loss) from rubber exploitation. Knowing the Net Profit of rubber business from latex and rubber wood. The research method uses purposive sampling method. Retrieval of data by collecting data using questionnaires-interviews, as well as by taking secondary data at the Village and District offices. The number of rubber plantation respondents was 30 people. Cost and income values are calculated in units of time per year. The results showed the average total cost of managing rubber plantation land was Rp.15.283,442 / year and the average total cost of cutting rubber wood was Rp.12.080,546 / ha. The average total income from processing rubber plantation land is Rp.35.997,000 / year and the average income of logging rubber is Rp.2.555,000 / ha. Based on data on costs, revenues and profits from the management of rubber plantation land amounting to Rp.20.731,558 / year and net benefits from logging of rubber wood Rp.1.474,454 / ha. While the Break Event Point (BEP) sales amounted to Rp.6.723,881 / ha / year and (BEP) in units of 1,034 kg / year / respondent.Keywords: Rubber garden; profit analysis; Village Jilatan Alur